A label-free DNAzyme-based nanopore biosensor for highly sensitive and selective lead ion detection. Issue 39 (15th September 2016) - Liu, Guangchao; Zhang, Ling; Dong, Duo; Liu, Yang; Li, Jinghong
Abstract : A single-molecule nanopore technique combined with a highly specific DNAzyme catalysis reaction has been employed to detect Pb 2+ . Abstract : As the lead ion (Pb 2+ ) can severely induce environmental pollution and harm human health, it is important to develop a simple, highly sensitive and selective sensor for Pb 2+ detection. Herein, a label-free DNAzyme-based nanopore biosensor for the sensitive and selective quantification of Pb 2+ has been developed. Pb 2+ can trigger the cleavage of a hairpin substrate in the presence of DNAzyme and cause the increase of single-stranded DNA (ssDNA) products, which could generate current blockade signals distinguished from that of the hairpin substrate when tested with an α-hemolysin nanopore. The presence of Pb 2+ can be detected at ∼3.48 nM or higher and the sensor is highly selective to Pb 2+ . Furthermore, the nanopore-based sensing strategy can be extended to other analytes which can trigger similar DNAzyme cleavage reactions.